2014
DOI: 10.1902/jop.2014.140042
|View full text |Cite
|
Sign up to set email alerts
|

Novel Implant Design Improves Implant Survival in Multirooted Extraction Sites: A Preclinical Pilot Study

Abstract: The novel design implants resulted in significantly greater survival rate in multirooted extraction sites. Further studies will be required to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Notably, 3 to 4 implants can be anchored per quadrant [ 284 ] with human or human-like implants 4 mm in diameter and 11 mm in length [ 286 ]. As for the tibia, the oral model may be useful for histological analyses such as cytotoxicity and viability of new compositions [ 287 , 288 , 289 , 290 ] but also for assessments on 1:1 scale models of mechanical properties [ 47 , 268 , 291 ], stress distribution [ 287 , 288 ], and the effects of different implant and abutment shapes [ 264 , 284 , 292 , 293 , 294 , 295 ]. Thanks to pigs having similar bone properties to those of humans, resistance to insertion [ 273 ] or removal torque can be measured during [ 296 ] or after healing [ 268 ].…”
Section: Appendix A1 Research In Non-human Primatesmentioning
confidence: 99%
“…Notably, 3 to 4 implants can be anchored per quadrant [ 284 ] with human or human-like implants 4 mm in diameter and 11 mm in length [ 286 ]. As for the tibia, the oral model may be useful for histological analyses such as cytotoxicity and viability of new compositions [ 287 , 288 , 289 , 290 ] but also for assessments on 1:1 scale models of mechanical properties [ 47 , 268 , 291 ], stress distribution [ 287 , 288 ], and the effects of different implant and abutment shapes [ 264 , 284 , 292 , 293 , 294 , 295 ]. Thanks to pigs having similar bone properties to those of humans, resistance to insertion [ 273 ] or removal torque can be measured during [ 296 ] or after healing [ 268 ].…”
Section: Appendix A1 Research In Non-human Primatesmentioning
confidence: 99%
“…Furthermore, stress distribution on short implants is affected by the bone-to-implant contact ratio [ 24 ]. Consequently, several options to increase the implant surface of short implants are elaborated, which consecutively enhance the implant stability: thread number, thread shape, thread depth, implant diameter, implant design and surface topography [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 In this context, recent studies have shown that in order to induce controlled compression forces in the cortical bone layer during implant insertion, a new hybrid auto-implant has been specifically designed for use in critical-quality bone, which combines the advantages of a conical implant with those of a cylindrical shape. 13 Considering the increase in the complexity of the cases in oral rehabilitations, modifications in the macro-geometry in implants should seek to favor their insertion, promoting the cut and bone compaction to increase their primary stability.…”
mentioning
confidence: 99%
“…Different implant designs were also tested by some authors in vivo and in vitro, 12,18,19 to increase the surface area of the implant with the bone tissue. Lundgren and colleagues, 18 and Sivan-Gildor and colleagues, 12 developed "hollow" implants in their inner portion and both concluded that the greater contact of the implant with the bone surface favored the success rate of these implants.…”
mentioning
confidence: 99%
See 1 more Smart Citation